Analisis Faktor Fundamental dan Non-Fundamental Terhadap Beta Saham Syariah Perusahaan Di Jakarta Islamic Index (JII) - Nova Sulistia; Tenny Badina; Rita Rosiana (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2020)
The purpose of this study to examine the effect of the variable Asset Growth, Debt to Asset Ratio, Net Profit Margin, Debt to Equity Ratio, Current Ratio, Stock Price, Exchange Rate, Inflation, and Gross Domestic Product on the beta of companies listed on the Jakarta Islamic Index (JII). The research period was for 8 years (2012-2019) with a total sample of 112 data. Data analysis uses panel data regression with a fixed effect model approach. The results show that the variable Debt to Asset Ratio, Net Profit Margin, Debt to Equity Ratio, Current Ratio, Stock Price, Exchange Rate, Inflation, Gross Domestic Product have a positive effect on stock beta, while Asset Growth variable has no effect on stock beta.